CASE REPORTSSequential development of multiple atherosclerotic peripheral arterial aneurysms in a four-year period - Göncü, Tugrul; Sezen, Mustafa; Vural, Hakan; Eris, Cüneyt; Yavuz, Senol; Ozyazicioglu, Ahmet (Archives of Medical Science, 2009)
Compared to the other isolated peripheral aneurysms, multiple peripheral aneurysms are less commonly encountered. We present a rare case of multiple aneurysms involving subclavian, bilateral popliteal and iliofemoral arteries which developed sequentially over a 4-year period. Histopathological studies of the specimens obtained from aneurysmal sacs demonstrated a correlation with atherosclerotic aneurysm. The aneurysms of the patient were successfully operated on sequentially at different times by using various surgical procedures. This case demonstrated that these patients should be monitored closely during their lifetime for development of new arterial aneurysms at different sites.